The Role of Actuarial Communicate Contemporary in Determining of Risks Insurance For Oman and the Western Countries from the Middle East - Abbad, . Jumah’; Shudifat, Omar (The Arab Journal of Administration, 2019)
The researchers studied the insurance sector in the Sultanate of Oman after being identified on the most important foundations of the actuarial studies in the Sultanate to achieve the role of Actuarial communicate, which aims to coordination and cooperation between the Arab countries to examine the financial situation of the reality of the insurance sector the Arab compared to other countries and the role of Actuarial communicate contemporary statement of those companies and the risks that may be suffered by the insurance sector. The study also came to know the reality of the insurance sector in the Western countries from the Middle East and what the risks might be exposed to and how to minimize the severity of those risks. Where the problem of the researchers of the financial indicators of companies engaged in insurance or reinsurance by which to determine the type of risk but cannot determine the amount of this risk and time of occurrence. So, the researchers developed hypotheses of this study was the main hypothesis, which states that there are no statistically significant differences between contemporary and Actuarial communicate risk insurance. And concluded the researchers in this study to the results that it was most important that the premiums written in the Sultanate of Oman on the rise with the passage of time is an indication to the high degree of risk rings the study’s recommendations was the most prominent that the local companies in the Sultanate’s development department specialized studies, actuarial, and that to expand the scope of activities insurance without resorting to the establishment of external studies in exchange for money or attract high insurance experts to study the adequacy of financial coverage in the development of new insurance activity.